The role of gamma oscillations in central nervous system diseases: Mechanism and treatment - Guan, Ao; Wang, Shaoshuang; Huang, Ailing; Qiu, Chenyue; Li, Yansong; Li, Xuying; Wang, Jinfei; Wang, Qiang; Deng, Bin (Frontiers in Cellular Neuroscience, 2022)
Neural oscillations are rhythmic electric activities of neuron groups in the brain, and gamma oscillation is the synchronization with a frequency of 30-90 Hz. The generation of gamma oscillations is dependent on inhibitory interneuron network, but it can be disrupted by some disturbances such as neural inflammation, oxidative stress and metabolic abnormalities. Gamma oscillations selectively regulate the connectivity across brain areas, which plays an important role in perception, motor, memory and emotion. Studies have demonstrated gamma oscillations disturbance associated with central nervous system diseases like Alzheimer's disease, Parkinson’s disease and schizophrenia, and evidence suggests that gamma entrainment using sensory stimulus (GENUS) offers significant neuroprotection. This review addresses the role of gamma oscillations in advanced brain functions at physiological and pathological status, and highlights gamma entrainment as a potential therapeutic operation in a variety of neuropsychiatric diseases.